2012
DOI: 10.1530/jme-12-0003
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PDGF-induced PI3 kinase activity by imatinib promotes adipogenesis and adiponectin secretion

Abstract: Improved glucose and lipid metabolism is a unique side effect of imatinib therapy in some chronic myeloid leukaemia (CML) patients. We recently reported that plasma levels of adiponectin, an important regulator of insulin sensitivity, are elevated following imatinib therapy in CML patients, which could account for these improved metabolic outcomes. Adiponectin is secreted exclusively from adipocytes, suggesting that imatinib modulates adiponectin levels directly, by transcriptional upregulation of adiponectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 56 publications
3
33
1
Order By: Relevance
“…32 Also proadipogenic effects of imatinib mesylate and dasatinib on multipotent mesenchymal stromal cells have been described. 33,34 In contrast to this, imatinib mesylate at a concentration of 2.5 lg/mL (the highest nontoxic concentration in our hands) blocked adipogenesis by orbital fibroblasts in our culture system (Supplementary Fig. S1), although not as efficient as dasatinib at that concentration.…”
Section: Figure 5 Effect Of Dasatinib On Adipogenesis In Orbital Fibcontrasting
confidence: 59%
“…32 Also proadipogenic effects of imatinib mesylate and dasatinib on multipotent mesenchymal stromal cells have been described. 33,34 In contrast to this, imatinib mesylate at a concentration of 2.5 lg/mL (the highest nontoxic concentration in our hands) blocked adipogenesis by orbital fibroblasts in our culture system (Supplementary Fig. S1), although not as efficient as dasatinib at that concentration.…”
Section: Figure 5 Effect Of Dasatinib On Adipogenesis In Orbital Fibcontrasting
confidence: 59%
“…These data imply that STI-571 positively regulates PPARγ and thus seemingly contradict the observations in our study. However, a recent study has found that these STI-571 effects on adipose and insulin homeostasis are attributed to its inhibition of PDFGR (40). We showed in this study that specific inhibition of c-Abl, either by RNA interference or by the timely administration of STI-571, has an antiadipogenic effect and interferes with PPARγ activity.…”
Section: Discussionmentioning
confidence: 59%
“…Adiponectin was capable of reversing imatinib resistance both in vitro (imatinib-resistant K562 CML cells) and in vivo [95]. Interestingly, imatinib improved glucose and lipid metabolism and increased adiponectin levels in CML patients by promoting adipogenesis via the suppression of PI3 kinase signaling downstream of plateletderived growth factor receptor (PDGFR) [96].…”
Section: Adiponectin Mpd and CMLmentioning
confidence: 99%